Water sustainability and the challenges of its application in the West Bank and Gaza Strip in Palestine - Rammal, Fuad Yousef; Alkhazzan, Bouchta (Journal of Humanities & Social Sciences, 2020)
This research paper aimed to touch base with the water issue and the requirements of its sustainability in the West Bank and Gaza Strip, as it is one of the major problems that mortgages development in its comprehensiveness and the security of the whole region, by analyzing the Palestinian water strategy extending from 2014 to 2032, and by comparing it with the requirements and elements of water sustainability mentioned in the related literature. The paper stood to achieve the requirements of water sustainability, with all its components. The paper faces basic challenges, the most important political of which is the domination of the Israeli occupation and its endless violations of Palestinian soil resources, on top of which is water. Other challenges of the institutionalized, material and environmental nature, this study confirmed the necessity of adopting a participatory approach between the different actors, sharing the risks between them, in addition to networking with international strategic partners to move forward in providing safe water supply and sanitation services and their sustainability in the field of study.
Keywords: water sustainability; Palestinian water policy; economic efficiency; environmental sustainability; social justice